Analysis of The Impact of Climate Change on The Vulnerability of Coastal Areas and Small Islands in Gili Air, North Lombok - Jupri, Ahmad; Ahyadi, Hilman; Purnamayanti, Juli; Rahmatullah, Dimas Rizky; Aqiela, Zulia; Royani, Andhini Dwi Mifta; Putri, Baiq Ega Zulqaidah; Riski, Danu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This research analyzes the impact of climate change on the vulnerability of coastal areas and small islands in Gili Air, North Lombok. Climate change, including rising temperatures and sea levels, is affecting coastal ecosystems, such as coral reefs which are vulnerable to bleaching and death. This study identifies a trend of increasing built-up land on Gili Air in the 2013-2022 period, which is caused by tourism promotion policies. The impact of this policy causes an increase in the number of tourists and local residents, which then increases the need for tourism supporting facilities. These land cover changes and development pressures increase Gili Air's environmental and economic vulnerability to climate change. These findings emphasize the importance of comprehensive adaptation and mitigation strategies to preserve the sustainability of ecosystems and the livelihoods of local residents.